Extensive cervicofacial and mediastinal subcutaneous emphysema after endodontic retreatment of a maxillary canine: A case report - M Buchbender; S Musazada; S Kreißel; C M Schmitt (Wolters Kluwer Medknow Publications, 2017)
The current case reports of an iatrogenic cervicofacial and mediastinal subcutaneous emphysema (SCE) after endodontic retreatment of a maxillary canine with the usage of a rubber dam. A 79-year-old woman was brought to the hospital with a swelling of the right side of her face and neck. A computed tomography (CT) was performed, and she was directly treated with intravenous antibiotic chemotherapy. Clinical examination and CT revealed a pronounced cervicofacial and mediastinal SCE. After treatment with intravenous antibiotic chemotherapy, the patient showed a decrease of the SCE and was discharged from the hospital. SCEs should be diagnosed at the earliest possible stage to manage an appropriate treatment. In case of misinterpretation of the signs and symptoms or a misdiagnosed SCE, it can become life threatening for patients. Therefore, every clinician should consider preventive measures to avoid such complications.